Excitation Transfer Engineering in Ce-Doped Oxide Crystalline Scintillators by Codoping with Alkali-Earth Ions - Auffray, Etiennette; Augulis, Ramunas; Fedorov, Andrei; Dosovitskiy, Georgy; Grigorjeva, Larisa; Gulbinas, Vidmantas; Koschan, Merry; Lucchini, Marco; Melcher, Charles; Nargelas, Saulius; Tamulaitis, Gintautas; Vaitkevicius, Augustas; et al. (Wiley-VCH Verlag, 2018)
Time-resolved spectroscopic study of the photoluminescence response to femtosecond pulse excitation and free carrier absorption at different wavelengths, thermally stimulated luminescence measurements and investigation of differential absorption are applied to amend the available data on excitation transfer in GAGG:Ce scintillators, and an electronic energy-level diagram in this single crystal is suggested to explain the influence of codoping with divalent Mg on luminescence kinetics and light yield. The conclusions are generalized by comparison of the influence of aliovalent doping in garnets (GAGG:Ce) and oxyorthosilicates (LSO:Ce and YSO:Ce). In both cases, the codoping facilitates the energy transfer to radiative Ce3+ centers, while the light yield is increased in the LYSO:Ce system but reduced in GAGG:Ce.
This work has been supported by the European Social Fund Measure No. 09.3.3-LMT-K-712 activity Improvement of Researchers Qualification by Implementing the World-Class R&D Projects, and by grant #14.W03.31.0004 of the Russian Federation Government. Authors are grateful to CERN Crystal Clear Collaboration and COST Action TD1401 "Fast Advanced Scintillator Timing (FAST)" for support of collaboration.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; excitation transfer; free carriers; multicomponent garnets; scintillators